Implementation of the Objective Weighting and Grey Relational Analysis Method for the Promotion of the Position of Chief Financial Officer - Abdullah, Muksin Hi; Abdurahman, Muhdar; A. Thais, Iswan; Hadad, Sitna Hajar (Universitas Teknokrat Indonesia, 2025)
The promotion of the Chief Financial Officer (CFO) position is a form of appreciation for performance, competence, and significant contribution to the organization's financial management. This promotion is expected to motivate individuals to continue to improve their professional competence and have a greater positive impact on the development of the organization in the future. Problems in the promotion of the CFO position often arise due to various factors, both from the internal side of the organization and individuals. One of the main problems is the lack of transparency in the performance appraisal process, where the criteria for promotion are not clear or not in accordance with the standards that have been set. Subjective factors in job appraisals can trigger employee dissatisfaction, especially if the decisions taken are more influenced by personal proximity than competence and achievements. This study aims to implement an objective and accurate decision support system in the promotion process for the position of CFO by applying the GRA method and objective weighting using the CRITIC method. The ranking results show the ranking of candidates in the promotion of the Chief Financial Officer position based on their respective evaluation scores. Candidate 7 took first place with the highest score of 0.1251, followed by Candidate 6 with a score of 0.1242, and candidate 4 was in third place with a score of 0.1101. This shows that Candidates 7 and 6 have a significant competitive advantage over other candidates for the position. Contribution to the promotion of the CFO position is crucial in ensuring that decisions made in the assessment of candidates are not only based on intuition or subjective considerations, but through a systematic, objective, and data-driven approach.